PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN APOTEK DI KABUPATEN JEPARA - Kartikawati Kusumaningrum; Ahmad Suriyadi Muslim; Galih Kurniawan (Yayasan Nusantara Hasana Berdikari, 2026)
Service quality is one of the important factors that greatly determines a company's success in retaining customers and increasing competitiveness. This study aims to determine the effect of service quality on customer satisfaction and its implications for purchasing decisions. This study uses a quantitative approach with a causal associative method. The research sample consisted of 400 respondents who were selected purposively according to the criteria of active consumers. The research instrument was a questionnaire with a Likert scale, while data analysis was performed using descriptive statistics and simple linear regression with the help of the SPSS application. Descriptive analysis results show that the average service quality score is in the high category with a value of 117.12 in the range of 85–124, while customer satisfaction has an average of 92.24 in the range of 67–100. The regression test proved that service quality had a positive and significant effect on customer satisfaction and impacted purchasing decisions, with a significance value of <0.05. This indicates that the better the service provided, the higher the level of satisfaction and consumer interest in making purchases. The findings of this study have practical implications for management to maintain and improve service aspects, such as speed and accuracy of service, friendliness of staff, and completeness of supporting facilities. Service quality improvement strategies have proven to be an important factor in strengthening satisfaction and encouraging sustainable purchasing decisions.